A descriptive study of call centre complaints and their management in a Western Cape EMS - Spicer, Richard Michael Frank (Division of Emergency Medicine, 2021)
Introduction Emergency medical services (EMS) play a vital role in addressing the high burden of disease posed by emergency conditions in low-to-medium income countries and it is vital to ensure that EMS care is of a high quality. Complaints and their management are an important mechanism in addressing individual patient concerns and ensuring accountability to the public. Expanding the role of complaints to effectively affect system-wide quality improvement requires knowledge of trends based on aggregated complaint data. This study aims to describe the volume and nature of complaints received by an urban EMS organisation in the Western Cape. Methodology A retrospective analysis was performed of all non-clinical complaints received for the 2018 calendar year by the call centre of a public EMS in Cape Town, South Africa. All complaint documents were collected and collated with the original case dispatch information. Complaints were categorised according to a standardised complaint coding taxonomy published previously. Complaint investigation outcomes and recommendations were analysed by themes identified during the study. Results A total of 156 complaints were received which referred to 172 patients. Complaints originated primarily from healthcare providers (72%) and patients or public (22%). Inter-facility transfers (73%) generated the most complaints. Encoding of complaint narratives revealed 302 individual service issues, which were classified into taxonomy derived domains (Clinical – 36%; Management – 44%; Relationship – 20%). The “Management” domain highlighted delay issues, accounting for 38% (116/302). Conclusion In this urban EMS, the majority of complaints are related to delays. Complaints were primarily lodged by other healthcare providers. Complaint rates lodged by patients and public are low, and would suggest that a unified and well publicised complaint mechanism is necessary, in order to increase public involvement in service quality improvement. Further research is recommended to validate a taxonomy for EMS complaints specifically.